Governing climate change : polycentricity in action? - Jordan, Andrew, 1968- (Cambridge : Cambridge University Press, 2018)
Climate change governance is in a state of enormous flux. New and more dynamic forms of governing are appearing around the international climate regime centred on the United Nations Framework Convention on Climate Change (UNFCCC). They appear to be emerging spontaneously from the bottom up, producing a more dispersed pattern of governing, which Nobel Laureate Elinor Ostrom famously described as'polycentric'. This book brings together contributions from some of the world's foremost experts to provide the first systematic test of the ability of polycentric thinking to explain and enhance societal attempts to govern climate change. It is ideal for researchers in public policy, international relations, environmental science, environmental management, politics, law and public administration. It will also be useful on advanced courses in climate policy and governance, and for practitioners seeking incisive summaries of developments in particular sub-areas and sectors. This title is also available as Open Access on Cambridge Core.
Governing climate change polycentrically : setting the scene / Andrew Jordan, Dave Huitema, Jonas Schoenefeld, Harro van Asselt and Johanna Forster -- International governance : polycentric governing by and beyond the UNFCCC / Harro van Asselt and Fariborz Zelli -- National governance: the state's role in steering polycentric action / Joana Setzer and Michal Nachmany -- Transnational governance : charting new directions post-paris / Harriet Bulkeley, Michele Betsill, Daniel Compagnon, Thomas Hale, Matthew Hoffmann, Peter Newell and Matthew Paterson -- City and subnational governance: high ambitions : innovative instruments and polycentric collaborations? / Jeroen van der Heijden -- Experimentation : the politics of innovation and learning in polycentric governance / Jan-Peter Vos and Fabian Schroth -- Entrepreneurship : a key driver of polycentric governance? / Elin Lerum Boasson -- Leadership and pioneership: exploring their role in polycentric governance / Duncan Liefferink and Rudiger K. W. Wurzel -- Diffusion : an outcome of and an opportunity for polycentric activity? / Jale Tosun -- Linkages : understanding their role in polycentric governance / Philipp Pattberg, Sander Chan, Lisa Sanderink and Oscar Widerberg -- Orchestration : strategic ordering in polycentric governance / Kenneth W. Abbott -- Policy surveillance : its role in monitoring, reporting, evaluating and learning / Joseph E. Aldy -- Harnessing the market : trading in carbon allowances / Katja Biedenkopf and Jorgen Wettestad -- Decarbonisation : the politics of transformation / Steven Bernstein and Matthew Hoffmann -- Transferring technologies : the polycentric governance of clean energy technology / Liliana B. Andonova, Paula Castro and Kathryn Chelminski -- Governing experimental responses : negative emissions technologies and solar climate engineering / Jesse Reynolds -- Adaptation : the neglected dimension of polycentric climate governance? / Robbert Biesbroek and Alexandra Lesnikowski -- Equity and justice in polycentric climate governance / Chukwumerije Okereke -- Legitimacy and accountability in polycentric climate governance / Karin Backstrand, Fariborz Zelli and Philip Schleifer -- Governing climate change : the promise and limits of polycentric governance / Andrew Jordan, Dave Huitema, Harro van Asselt and Johanna Forster.
Title from publisher's bibliographic system (viewed on 15 May 2018).
Keywords: Climatic changes -- Interenational cooperation; Environmental policy -- International cooperation; United Nations Framework Convention on Climate Change (Organization)